Investigations into strength endurance exercises for swimmers - Witt, M.; Götz, J.-K. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: Training at specific power training devices plays a crucial role with the increase of drive power in cyclic motions. Similar to the competition movement the intensity is increased by an enhanced frequency. The temporal relationship of the driving phase and the break changes to the disadvantage of the break. We could show that the duration of the relative breaks is related positively to breathing economy. Thus in this study the behavior of muscle activity in the main drive muscles in case of increased frequency was analyzed. METHODS: 12 age-group swimmers performed both the classical pulling movement of swimmers (butterfly, front crawl) at a rope pulling ergometer as well as the single and double pole skiing techniques. In each case the frequency was increased by 30 to 50 reps/min . At the rope pulling ergometer (FES Berlin) we monitored the force-distance curves of intra-cyclic power, frequency, stroke length and duration as well as the activities of several arm and shoulder muscles (Myo 2000, Noraxon). From the EMG the mean relative activity (% MVC) as well as the activity duration (tM) was calculated. RESULTS: In all kinds of movement the intra-cyclic power increased with the frequency, with higher values in the synchronous pulling techniques compared to the alternating techniques just like in the comparison of the ski pulling techniques with the swimming techniques. The duration of the break decreased in relation to the stroke time with all kinds of movement. The highest relative activities were monitored for m. pectoralis major (PM) and m. latissimus dorsi (LD), their muscle activity increased simultaneously with intra-cyclic power during frequency increase. Altogether muscle activity in swimming was higher than in skiing. The relative duration of muscular activity increased simultaneously with the relative duration of the pulling phase during the higher frequencies, with some muscles showing higher activity duration during lower frequencies. Table: Relative duration of the recovery phase of PM and LD in relation to the stroke duration during different stroke rates (SR): SR [1/min] 30; 35; 40; 45; 50; PM [%] 61 ± 10,6; 59 ± 11,6; 58 ± 10,2; 53 ± 13,0; 47 ± 15,8; LD [%] 46 ± 15,4; 48 ± 16,0; 51 ± 10,8; 47 ± 9,8; 40 ± 8,6; DISCUSSION: The LD and PM could be identified as main drive muscles for all kind of techniques. Thus the ski pulling techniques represent a suitable training exercise for the power endurance development of the swimmers.